Mechanisms of Pathogenesis in Listeria monocytogenes Infection IV. Hepatic Carbohydrate Metabolism and Function in Experimental Listeriosis - McCallum, R. E. (1970)
Previous reports have shown alterations in carbohydrate metabolism in mice infected with Listeria monocytogenes. This study was undertaken to elucidate mechanisms involved in these changes. Female CD-1 mice were injected intraperitoneally with 10(6)L. monocytogenes strain A4413. Animals were fasted 12 hr prior to infection, and pooled tissue from several mice was observed at intervals after infection. Blood glucose, liver glucose, and liver glycogen decreased within 10 hr after infection. Sustained treatment with gluconeogenic precursors, including glucose-6-phosphate, fructose-1, 6-biphosphate, phosphoenolpyruvate, α-glycerophosphate, pyruvate, and amino acids, did not restore and maintain glucose and glycogen at normal levels and did not affect survival. Administration of hydrocortisone induced restoration of liver glycogen early in the infection but did not maintain normal levels as the infection progressed. Activities of succinic dehydrogenase and cytochrome oxidase in liver homogenates from infected mice were elevated as early as 10 hr after infection. Liver function tests using rose bengal sodium-(131)I showed no significant differences in plasma clearance or liver uptake between normal and infected mice except in terminal infections (60 hr after infection).